Islamic asset management (Journal of Philosophy Culture and Political Science, 2019)
Abstract. This article looks at the development and growth of lslamk investment funds through the prism of several key asset classes. In the course of the article, past existing and recently innovated investment products provide a template for understanding the Islamic asset management process. The product examples illustrate the ways in which the development of the Islamic fund management capability has benefi ted the entire Islamic fi nancial sector. Is three greater opportunity for effi cient portfolio diversifi cation, and if not, why not? What has impedance development, and what is the extent of those impediments? This article aims to offer an insight to these issues and, hopefully, the solutions. Equity investment, as a key topic in this article, provides an interesting illustration of Islamic fund structuring and also demonstrates one or two of the elements that have consistently been proven critical to the successful launch of an Islamic investment fund. Keywords: Islamic banking, takaful, salam salam sukuk and Murabaha.